Faktor-Faktor Yang Mempengaruhi Produksi Padi Sawah Di Desa Minanga Satu Kecamatan Pusomaen Kabupaten Minahasa Tenggara - Pangkerego, Thessalonika Yemima Rosario; Kapantow, Gene Henfried Meyer; Maweikere, Audrey Julia Maria (Sam Ratulangi University, 2024)
This study aims to determine the factors that influence the production of paddy rice in Minanga Satu Village, Pusomaen District, Southeast Minahasa Regency. The sampling method was carried out using the Random Sampling method, namely by random sampling. The data collected are primary and secondary data with multiple linear regression analysis and using the Cobb-Douglass production function model. Based on the results of research that has been done in Minanga Satu Village, Pusomaen District, Southeast Minahasa Regency, and based on the research objectives, it can be concluded that together (simultaneously) the variables of land area, labor, seeds, Urea fertilizer, Phonska fertilizer, and pesticides have a relationship to the amount of production of paddy rice in Minanga Satu Village, Pusomaen District, Southeast Minahasa Regency. Partially, the factors of land area, labor, phonska fertilizer have a significant effect, while seeds, urea fertilizer, and pesticides do not have a significant effect on the production of paddy rice in Minanga Satu Village, Pusomaen District, Southeast Minahasa Regency.